2021
DOI: 10.4103/lungindia.lungindia_198_20
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome

Abstract: Context: In this autopsy study, the various morphological patterns of acute respiratory distress syndrome (ARDS) have been analyzed and compared along with their etiopathogenesis. Aims: We aimed to study the prevalence and clinicopathological correlation of ARDS based on age, gender, hospital stay, symptoms, clinical diagnosis, gross, and microscopy findings. Subjects and Methods: Total 130 cases of ARDS were studied over a period of 5 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…37 Our comparison of mice in the Control group with mice in the LPS group revealed that sepsis modeling significantly worsened the pulmonary edema of mice and significantly increased the pulmonary pathological damage score. These pathological changes were consistent with the conclusions of clinical studies 38,39 focusing on the pulmonary characteristics of patients with sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…37 Our comparison of mice in the Control group with mice in the LPS group revealed that sepsis modeling significantly worsened the pulmonary edema of mice and significantly increased the pulmonary pathological damage score. These pathological changes were consistent with the conclusions of clinical studies 38,39 focusing on the pulmonary characteristics of patients with sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…Macroscopic and microscopic autopsy findings in the lungs of those who died within the first 24 h after hospitalization were characterized by interstitial edema and hemorrhage in lungs [ 70 ] and tubular degeneration in the kidney (acute tubular necrosis); also, in those who died later after OP poisoning [ 75 , 76 , 77 , 78 , 79 , 80 ], the findings mostly resemble those observed in people who died of acute respiratory distress syndrome (ARDS) [ 81 , 82 ] of different causes, including viral infections of the upper respiratory tract [ 83 , 84 , 85 , 86 ] and also paraquat intoxication [ 87 ]. Similar histopathological (microscopic) changes can be induced in minipigs by bronchoscopic instillation of gastric juice containing OP (40% dimethoate 0.5 mL/kg) into the lung [ 88 ], simulating aspiration of gastric content, as may happen after ingestion of the insecticide mostly with suicidal intention.…”
Section: Organophosphorus Compounds As Insecticides and As Nerve Agentsmentioning
confidence: 99%
“…Autopsies are seldom performed in patients who died because of AOPP, and in most cases, it is related to the search for the toxic agent [ 77 , 78 , 79 , 80 , 81 , 82 ] and less to mechanisms that lead to death such as cardiac arrest, especially in persons of young age.…”
Section: Acetylcholinesterase and Albumin Measurement: Importance For...mentioning
confidence: 99%